(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): What is the impact of leadership and organizational culture on processes, innovation, and results in manufacturing companies within the EFQM model framework? Purpose: The purpose of this paper is to review articles that use the EFQM model as a theoretical framework. With its help, we analyse the relationships between leadership, organizational culture, innovation, effective resource management, and financial performance in manufacturing and related organizations. Special emphasis is placed on how leadership influences the achievement of results through EFQM model factors. Specifically, its impact on outcomes for customers, employees, society, and key business indicators. Method: A targeted review of eleven original scientific articles was conducted. Two EFQM model documents were also included. The articles were selected from the SCOPUS database. The analysis was based on a qualitative approach. A qualitative thematic synthesis was developed from the analysis of individual studies, grouping the findings into seven thematic categories. This approach enables the identification of common patterns of leadership influence on processes and results within the logic of the EFQM 2013 model and EFQM 2020 models. Results: The literature review shows that leadership plays a central role in applying the EFQM model. It influences the formation of a stable and process-oriented organizational culture. Soft factors (leadership, people, culture) operate through technical factors such as processes, partnerships, and resources. Together, they affect innovation, quality, cost efficiency, and financial outcomes. Studies indicate that a stable, hierarchical, or market-oriented culture is often most suitable for implementing EFQM model criteria in manufacturing companies. They support discipline, accountability, and a results-oriented mindset. Leadership also strengthens the connection between process management and performance, while further promoting innovation practices, efficient use of resources, and sustainability effects. These findings are consistent with the logic of the EFQM 2013 and EFQM 2020 models. Organization: The research shows that leadership and organizational culture play a crucial role in shaping processes, innovation, and business results in manufacturing companies within the EFQM framework. Soft factors (leadership, people, culture) influence improvements in quality, efficiency, and financial performance through processes, partnerships, and resource management. Society: The consistent application of EFQM models principles also contributes to broader societal benefits. They include responsible resource management, more efficient energy use, and sustainable value creation for stakeholders. Originality: The study links leadership, organizational culture, and the performance of manufacturing companies across both versions of the EFQM models (2013 and 2020). The thematic synthesis of seven categories offers a comprehensive insight into how leadership, through culture, guides processes and promotes innovation and sustainable improvements. Limitations/Future Research: The review is limited to eleven scientific articles and two official EFQM model documents. These may narrow the scope of the findings. Future research should examine the impact of specific leadership practices on EFQM models outcomes, compare the use of EFQM models with other models such as ISO 9001. They should examine lean manufacturing and explore the influence of digital transformation on how the model functions.